2021
DOI: 10.1057/s41283-021-00077-4
|View full text |Cite
|
Sign up to set email alerts
|

Is the ESG portfolio less turbulent than a market benchmark portfolio?

Abstract: Given that there is no consensus on the fact that ESG portfolios are characterized by very high returns and very low risks compared to conventional portfolios, this study aims to empirically verify whether the series of returns of an ESG portfolio is less volatile than the returns of a benchmark market portfolio. To verify this hypothesis, we used the Markov-switching GARCH models in order to model the process of the series of daily returns of the ESG portfolio "MSCI USA ESG Select," as well as those of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…This finding is even clearer for the estimates related to the pandemic period. The volatility analysis shows that the COVID-19 pandemic increased the contagion risk, but the sustainable funds had a superior ability to face this type of risk, as was already reported by Ouchen [35] for an ESG portfolio.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This finding is even clearer for the estimates related to the pandemic period. The volatility analysis shows that the COVID-19 pandemic increased the contagion risk, but the sustainable funds had a superior ability to face this type of risk, as was already reported by Ouchen [35] for an ESG portfolio.…”
Section: Discussionsupporting
confidence: 58%
“…For example, Biasin et al [32]-one of the last studies before the pandemic-highlight the benefits of social impact investmentbased portfolios. Abate et al [33], using a sample of European funds, and Das et al [34] showed that socially responsible mutual funds outperformed conventional funds and Ouchen [35] demonstrated that the ESG portfolio MSCI USA ESG Select was "less turbulent". Meanwhile, Becchetti and Ciciretti [36], analyzing the volatility issue in greater depth, found that individual socially responsible stocks are significantly less risky when controlling for conditional heteroskedasticity.…”
Section: Related Literaturementioning
confidence: 99%
“…This implies that investment in ESG indices may provide equally good or even better returns while pursuing an ethics-focused investment strategy. Ouchen (2021) empirically verified whether the series of returns of an ESG index was less volatile than that of a conventional stock index. He concluded that the ESG index was relatively less turbulent than the stock index.…”
Section: Introductionmentioning
confidence: 90%
“…ESG investing exhibits positive characteristics during turbulent markets such as during the COVID-19 market shock [16]. Looking back to the year 2020, the market experienced anxiety and uncertainty due to the coronavirus outbreak, and declined, between February and March 2020, by more than 30%.…”
Section: Positive Implications Of Esg Investingmentioning
confidence: 99%